Mengkritisi Hadis-Hadis Tentang Usia Pernikahan Aisyah - Rahmah, Wahyuni Shifatur (Musawa Jurnal Studi Gender dan Islam, 2009)
Muslim scholars disagree as how old lady Aisyah was when she married Prophet Muhammad. One of the popular records reported by Hisyam bin Urwah says that she was about 6 and 9 years old. However, more recent careful study of hadits shows that the Hisyam bin Urwah's version of report is contradictory with other available reports, and therefore the validity of the hadits is in doubt. Nonetheless it is both interesting and strange to see how the hadits has been used as a valid argument by opponents of Islam to destroy the image of the Prophet and Islamic teaching in general, and even by Muslims themselves to justify their interests to take advantages of marrying young girls. This paper aims at reexamining the aunthenticity and validity of the hadits reported by Hisyam bin Urwah regarding the marriage lady Aisyah with Prophet Muhammad.